Математичне моделювання течії середовища через лабіринтове ущільнення турбомашини - Пустовалов, Володимир Миколайович; Фатіч, Л. В.; Науменко, Світлана Петрівна (НТУ "ХПІ", 2015)
Проведено математичне моделювання гідродинаміки і тепловіддачі потоку середовища у прямоточному та ступінчатому лабіринтових ущільненнях турбомашин за допомогою комплексу прикладних програм. Зіставлення результатів з відповідним фізичним експериментом показало адекватність використаного підходу і обґрунтовувало можливість застосування його при розв’язанні конкретних інженерних задач.

Labyrinth seals used by modern high-power steam and gas turbines occupy a considerable portion of the rotor surface and casing components. For example, the labyrinth seals of the high-pressure cylinder of the steam turbine operated by PJSC "Turboatom" K-325-24.5 take up 60 % of its length. Hence, for the appropriate identification of the thermal, thermally stressed and thermally strained state of the high pressure parts of such turbines we need to have more accurate data on the boundary conditions of the heat exchange in labyrinth seals. This is of great importance for the mathematical simulation whose purpose is to search for the optimal start –up schedule of high power steam turbines from different initial states. In the paper, mathematical modeling of fluid flow and heat transfer in in-line flow and stepped labyrinth turbomachinery seals was carried out using an application package. Comparison of the results with physical experiments have shown the adequacy of modeling and the ability to use it in solving specific engineering problems.
Mathematical simulation of the medium flow through the labyrinth seal of the turbomachine
Keywords: турбоустановки; гідродинаміка; тепловіддача; комплекс прикладних програм; turbomachines; labyrinth seals; hydrodynamics; heat emission; mathematical simulation